2022
DOI: 10.1002/ccr3.5408
|View full text |Cite|
|
Sign up to set email alerts
|

Atypical presentation of adenosine deaminase 2 deficiency with bi‐allelic ADA2 mutation

Abstract: Herein, we report a case of VAIHS with atypical clinical presentation of perianal abscess, fistula fever, and bi‐cytopenia including pathogenic ADA2 mutation suggesting that ADA2 deficiency be considered as a differential diagnosis of enlarging cutaneous abscess with no evidence of wound healing in the setting of leukopenia and neutropenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…Until recently, only two DADA2 patients have been reported to present overlapping inflammatory and hematologic phenotypes: Al-shaikh et al reported the case of an 18-month-old DADA2 patient presenting recurrent fever, persistent neutropenia, oral aphthous ulcers, and skin abscess, which did not respond to IV methylprednisolone, Intravenous immune globulin (IVIG), Granulocyte colony-stimulating factor (G-CSF), or infliximab. The febrile episodes responded to therapy with IL-1 inhibitor, anakinra, but the patient eventually perished due to persistent perirectal mass bleeding and multiple organ failure ( 18 ). A patient reported by Göschl et al presented neutropenia, recurrent fever, and oral ulcers and later hypogammaglobulinemia, from 8 to 24 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Until recently, only two DADA2 patients have been reported to present overlapping inflammatory and hematologic phenotypes: Al-shaikh et al reported the case of an 18-month-old DADA2 patient presenting recurrent fever, persistent neutropenia, oral aphthous ulcers, and skin abscess, which did not respond to IV methylprednisolone, Intravenous immune globulin (IVIG), Granulocyte colony-stimulating factor (G-CSF), or infliximab. The febrile episodes responded to therapy with IL-1 inhibitor, anakinra, but the patient eventually perished due to persistent perirectal mass bleeding and multiple organ failure ( 18 ). A patient reported by Göschl et al presented neutropenia, recurrent fever, and oral ulcers and later hypogammaglobulinemia, from 8 to 24 years of age.…”
Section: Discussionmentioning
confidence: 99%